Agronomic strategies to enhance the early vigor and yield of maize. Part I: the role of seed applied biostimulant, hybrid and starter fertilization on rhizosphere bacteria profile and diversity - Ujvári, Gergely; Capo, Luca; Grassi, Arianna; Cristani, Caterina; Pagliarani, Irene; Turrini, Alessandra; Blandino, Massimo; Giovannetti, Manuela; Agnolucci, Monica (Frontiers in Plant Science, 2023)
The sustainable intensification of maize-based systems may reduce greenhouse-gas emissions and the excessive use of non-renewable inputs. Considering the key role that the microbiological fertility has on crop growth and resilience, it is worth of interest studying the role of cropping system on the rhizosphere bacterial communities, that affect soil health and biological soil fertility. In this work we monitored and characterized the diversity and composition of native rhizosphere bacterial communities during the early growth phases of two maize genotypes of different early vigor, using a nitrogen (N)-phosphorus (P) starter fertilization and a biostimulant seed treatment, in a growth chamber experiment, by polymerase chain reaction-denaturing gradient gel electrophoresis of partial 16S rRNA gene and amplicon sequencing. Cluster analyses showed that the biostimulant treatment affected the rhizosphere bacterial microbiota of the ordinary hybrid more than that of the early vigor, both at plant emergence and at the 5-leaf stage. Moreover, the diversity indices calculated from the community profiles, revealed significant effects of NP fertilization on richness and the estimated effective number of species (H2) in both maize genotypes, while the biostimulant had a positive effect on plant growth promoting community of the ordinary hybrid, both at the plant emergence and at the fifth leaf stage. Our data showed that maize genotype was the major factor shaping rhizosphere bacterial community composition suggesting that the root system of the two maize hybrids recruited a different microbiota. Moreover, for the first time, we identified at the species and genus level the predominant native bacteria associated with two maize hybrids differing for vigor. These results pave the way for further studies to be performed on the effects of cropping system and specific crop practices, considering also the application of biostimulants, on beneficial rhizosphere microorganisms.